Pemodelan Sistem Dinamis Economy-Energy Dalam Pengurangan Emisi Co2 Dan Peningkatan Pdrb Untuk Meningkatkan Ketahanan Daerah Banten - Yoesgiantoro, Donny; Sumiati, Sumiati (Jurnal Kajian Stratejik Ketahanan Nasional, 2018)
Banten Province is one of the areas in Indonesia that has a similar characteristics. Although Banten has an important role in regional and national economic growth, but the region is also included as a contributors of CO2 emissions and consume a substantial amounts of fossil energy. Areas like this endure two opposite sides. On one side, economic growth as an important aspect of regional growth, on the other hand there is an tremendous increase in CO2 emissions. government policies to reduce CO2 emissions can not be determined equally, although among the Provinces have similar characteristics and their effects on global CO2 emissions. making a policy concerning complex issues such as CO2 emission reduction require a dynamic system modeling with the EECP concept. Model concept is made into Causal Loop Diagram using vensim software, then implemented to equation in Stock Flow Diagram using Powersim software, then simulated and analyzed. In this study determined two policies as an effort to reduce CO2 emissions that is the use of renewable energy scenarios and the implementation of the carbon tax. The results show that the implementation of a carbon tax more than Rp.80.000, - will boost the interest of industry Stakeholder shifting the use of fossil energy into renewable energy. Both policies can contribute Supressing CO2 emissions in Banten province, thereby providing the effect of CO2 emission reduction on global warming that threatens the mandkind.